2011
DOI: 10.1007/s00040-011-0214-6
|View full text |Cite
|
Sign up to set email alerts
|

Queen signal should be honest to be involved in maintenance of eusociality: chemical correlates of fertility in Ropalidia marginata

Abstract: Queens of many social insect species are known to maintain reproductive monopoly by pheromonal signalling of fecundity. Queens of the primitively eusocial wasp Ropalidia marginata appear to do so using secretions from their Dufour's glands, whose hydrocarbon composition is correlated with fertility. Solitary nest foundresses of R. marginata are without nestmates; hence expressing a queen signal can be redundant, since there is no one to receive the signal. But if queen pheromone is an honest signal inextricabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…This may be another example of an adaptation of Dufour's gland secretions for a function not reported in other hymenopteran taxa. In Polistinae, Dufour's gland compounds have been implicated in dominance interactions, egg marking, nestmate recognition, and queen signaling (Downing and Jeanne 1983, Downing 1991, Dani et al 1996a, 1996b, Mitra and Gadagkar 2012a, 2012b. In the polistine wasp Ropalidia marginata the Dufour's gland has been shown to be involved in producing the queen pheromone, using which the queen conveys her presence to workers and thereby maintains reproductive monopoly .…”
Section: B) Aculeatamentioning
confidence: 99%
See 1 more Smart Citation
“…This may be another example of an adaptation of Dufour's gland secretions for a function not reported in other hymenopteran taxa. In Polistinae, Dufour's gland compounds have been implicated in dominance interactions, egg marking, nestmate recognition, and queen signaling (Downing and Jeanne 1983, Downing 1991, Dani et al 1996a, 1996b, Mitra and Gadagkar 2012a, 2012b. In the polistine wasp Ropalidia marginata the Dufour's gland has been shown to be involved in producing the queen pheromone, using which the queen conveys her presence to workers and thereby maintains reproductive monopoly .…”
Section: B) Aculeatamentioning
confidence: 99%
“…In the polistine wasp Ropalidia marginata the Dufour's gland has been shown to be involved in producing the queen pheromone, using which the queen conveys her presence to workers and thereby maintains reproductive monopoly . It has also been found that the Dufour's gland hydrocarbon composition varies as a function of ovarian development, thereby suggesting that such chemicals can act as an honest signal of the queen's fertility , Mitra and Gadagkar 2012a, 2012b. Interestingly it has been found that the cuticle and the haemolymph of R. marginata also contain the same set of hydrocarbons as found in the Dufour's gland, thereby implying that these hydrocarbons can be synthesized in the oenocytes of fat bodies, from where they enter circulation in the haemoplymph and are finally sequestered and stored in the Dufour's gland or secreted on the cuticle (Mitra and Gadagkar: in press).…”
Section: B) Aculeatamentioning
confidence: 99%
“…; Mitra et al. ; Mitra & Gadagkar ,). This suggests that the mechanism of maintenance of eusociality, believed to be through aggression shown by the queen in typical primitively eusocial species (Wilson ; Keller & Nonacs ), has shifted to pheromonal queen signaling in R. marginata , similar to what is seen in highly eusocial species.…”
Section: Introductionmentioning
confidence: 98%
“…; Mitra et al. ; Mitra & Gadagkar , ), PQs can be expected to be similar to queens by the time they have developed their ovaries. However, it is not known whether PQs are initially similar to workers in their Dufour's gland hydrocarbons, on account of having undeveloped ovaries, or whether they can be differentiated from workers even at an initial stage.…”
Section: Introductionmentioning
confidence: 99%
“…We now have growing evidence that they nevertheless manage to maintain reproductive monopoly by means of pheromones [28][29][30][31][32]. Also unexpected for a typical primitively eusocial species, queens of R. marginata do not appear to be involved in the regulation of colony labour.…”
Section: Meek Docile Queens and Decentralized Work Organizationmentioning
confidence: 99%